Melting the Content, Pedagogy and Technology in the Same Pot: Insights into EFL Instructors’ TPACK Perceptions in Digital Era - Da?göl, Gökçe Di?len (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Digital era necessitates not only knowledge of content and teaching methods but also integration of technology in language instruction. Covid-19 pandemic has constituted one of the critical reasons that accelerated the inclusion of digital tools into the teaching practice. Â Using the technological pedagogical and content knowledge framework, the present study dwelled upon the EFL instructorsâ€™ perceived TPACK levels and the probable changes that they experienced in their technological skills and knowledge after pandemic. The EFL instructors working at both state and private universities formed the participants of the study. Based on the mixed research method, the study gathered the data were both quantitatively and qualitatively. The quantitative data were collected through TPACK-Deep Scale and, open-ended question form was administrated for the qualitative data. The results indicated that EFL instructors had higher perceptions of TPACK, and they had differing levels for each factor level depending on gender, workplace, years of experience and educational status. They also mainly experienced positive changes after pandemic and had favorable attitudes towards technology use in language teaching. Finally, the study suggested pedagogical implications to benefit from technology for instructional purposes.